Health-promoting effects of Thymus phenolic-rich extracts: antioxidant, anti-inflammatory and antitumoral properties - Fernandes Afonso, Andrea Luísa (2020)
Thymus genus comprises numerous species that are particularly abundant in the West Mediterranean region. A growing body of evidence suggests that many of these species are a rich source of bioactive compounds, including phenolic compounds such as rosmarinic acid, salvianolic acids and luteolin glycosides, able to render them potential applications in a range of industrial fields. This review collects the most relevant studies focused on the antioxidant, anti-inflammatory and anti-cancer of phenolic-rich extracts from Thymus plants, highlighting correlations made by the authors with respect to the main phenolic players in such activities.